Komparasi Aplikasi Perangkat Lunak Sistem Klasifikasi DDC: Athenaeum Light 8.5, DFW Version 1.00, Webdewey 2.0, E-DDC Edition 22 - Hardiati, Wijaya (Pustakaloka, 2012)
Librarian has many alternative to classify DDC (Dewey Decimal Classification) number. not only use printed DDC, but now DDC software to help identify DDC number is available. One of them is Athenaeum Light 8.5, DFW (Dewey For Windows) Version 1.00, WebDewey 2.0, e-DDC (electronic-Dewey Decimal Classification) Edition 22. In this paper, it will roll out about how to use software with it excess and deficiency.